SELECTION MODELS OF THE JAYA UTAMA AND SUGENG RAHAYU BUS ROUTES USING THE STAGED LOADING METHOD (CASE STUDY: PURABAYA TERMINAL – TERBOYO TERMINAL - Fauzan Rokhimi; Nugroho Utomo; Ibnu Sholichin (CI-TECH, 2022)
SELECTION MODELS OF THE JAYA UTAMA AND SUGENG RAHAYU BUS ROUTES USING THE STAGED LOADING METHOD (CASE STUDY: PURABAYA TERMINAL – TERBOYO TERMINAL